2016
DOI: 10.1016/j.molimm.2016.08.004
|View full text |Cite
|
Sign up to set email alerts
|

LPS injection reprograms the expression and the 3′ UTR of a CAP gene by alternative polyadenylation and the formation of a GAIT element in Ciona intestinalis

Abstract: a b s t r a c tThe diversification of cellular functions is one of the major characteristics of multicellular organisms which allow cells to modulate their gene expression, leading to the formation of transcripts and proteins with different functions and concentrations in response to different stimuli. CAP genes represent a widespread family of proteins belonging to the cysteine-rich secretory protein, antigen 5 and pathogenesis-related 1 superfamily which, it has been proposed, play key roles in the infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In humans, GAIT elements are implicated in several immune-related mRNAs, showing an important role in gene-specific translation control in innate immunity 54 . In C. robusta, GAIT elements have already been identified in Cap 55 and Tnf-α 56 and in Mif mRNAs 45 . Notably, in C. robusta, Mifs also seem to regulate Mmp9, which has several important immune functions, such as extracellular matrix degradation and Tnf-α and Tgf-β activation 57 .…”
Section: Discussionmentioning
confidence: 99%
“…In humans, GAIT elements are implicated in several immune-related mRNAs, showing an important role in gene-specific translation control in innate immunity 54 . In C. robusta, GAIT elements have already been identified in Cap 55 and Tnf-α 56 and in Mif mRNAs 45 . Notably, in C. robusta, Mifs also seem to regulate Mmp9, which has several important immune functions, such as extracellular matrix degradation and Tnf-α and Tgf-β activation 57 .…”
Section: Discussionmentioning
confidence: 99%
“…The urochordate sea squirt Ciona intestinalis exhibits a structural equivalent of a GAIT element in the 3 0 -UTR of a CAP gene member of the cysteine-rich secretory protein, antigen 5 and pathogenesis-related 1 superfamily thought to be involved in modulation of host immune responses. 130 Interestingly, formation of the GAIT is regulated, and only forms when the organism is challenged with LPS, consistent with a role in innate immunity. Genome sequencing of C. intestinalis revealed that EPRS mRNA contains two WHEP domains comparable to the RNA-binding, upstream pair of WHEP domains in the human ortholog, suggesting a potential GAIT element-binding activity of EPRS and GAIT-mediated innate immune function.…”
Section: Evolution and Conservation Of The Gait Systemmentioning
confidence: 82%
“…There is no experimental evidence for the presence of GAIT function in more complex, i.e., bilaterial, metazoans other than mice and humans. The urochordate sea squirt Ciona intestinalis exhibits a structural equivalent of a GAIT element in the 3′‐UTR of a CAP gene member of the cysteine‐rich secretory protein, antigen 5 and pathogenesis‐related 1 superfamily thought to be involved in modulation of host immune responses . Interestingly, formation of the GAIT is regulated, and only forms when the organism is challenged with LPS, consistent with a role in innate immunity.…”
Section: Evolution and Conservation Of The Gait Systemmentioning
confidence: 99%
“…LPS) has been described (Vizzini et al, 2016). In the ascidian Ciona intestinalis a novel alternative polyadenylation signal activated by the prototypical TLR4 agonist (i.e.…”
Section: Figure 26mentioning
confidence: 99%